Corrosion behavior of nanocrystalline CoNiFe electrodeposited on stainless steel / Nor Azrina Resali - Resali, Nor Azrina (Institute of Graduate Studies, UiTM, 2015)
The stainless steels are become more susceptible to localized corrosion when they are exposed to harsh environments. This study is to deposit an alternative material focusing on nanocrystalline CoNiFe which has been identified as a potential candidate for replacing hexavalent chromium plating in corrosion resistant coating. This material is recognized as a green material because it does not hazardous to environment. The objectives of this research are to optimize the deposition parameters in synthesise nanocrystalline CoNiFe coating layer on stainless steel and heat treat it to obtain optimum corrosion properties in suitable environments. The CoNiFe coating was synthesised using an electrodepostion process by varying pH solutions (3, 7 & 9) and deposition times (30, 60 & 90 minutes) in order to determine the optimum deposition parameters. Other parameters such as electrolyte composition, temperature and current density were kept constant. The heat treatment process was conducted at the optimum heat treatment temperature of 700oC under two different inert gas atmospheres, which are 100% argon and mixture of 95% 10 argon + 5% hydrogen gases. Lastly, the corrosion behaviour of nanocrystalline CoNiFe with and without heat treatment under various environments was determined…